2021
DOI: 10.1101/2021.10.28.466343
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Compartmentalized dendritic plasticity in the retrosplenial cortex integrates memories across time

Abstract: Events occurring close in time are often linked in memory, providing an episodic timeline and a framework for those memories. Recent studies suggest that memories acquired close in time are encoded by overlapping neuronal ensembles, and that this overlap is necessary for memory linking. Transient increases in neuronal excitability drive this ensemble overlap, but whether dendritic plasticity plays a role in linking memories is unknown. Here, we show that contextual memory linking is not only dependent on ensem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Here, we demonstrate the MiniLFOV enables single cell resolution across the entire FOV ( Fig. 5a ) by imaging GCaMP6f-expressing dorsal cortex 44,45 through a 4 mm × 4 mm cranial window in head-fixed mice running on a 29-mm circular treadmill ( Fig. 5a, s12a ).…”
Section: Resultsmentioning
confidence: 86%
“…Here, we demonstrate the MiniLFOV enables single cell resolution across the entire FOV ( Fig. 5a ) by imaging GCaMP6f-expressing dorsal cortex 44,45 through a 4 mm × 4 mm cranial window in head-fixed mice running on a 29-mm circular treadmill ( Fig. 5a, s12a ).…”
Section: Resultsmentioning
confidence: 86%
“…Here, we built a model that is able to reproduce the overlap among memory engrams of events that are temporally linked. These overlaps have been observed in the amygdala (Rashid et al ., 2016), the hippocampus (Cai et al ., 2016) and the retrosplenial cortex (Sehgal et al ., 2021) while it has been reported that these three regions are involved in a memory consolidation process known as systems consolidation (Tonegawa et al ., 2018; Kitamura et al ., 2017). However, it remains unclear what information is transferred from one region to another and investigating a potential transfer of overlap between brain regions would help understand how temporal memory linking evolves over the course of systems consolidation.…”
Section: Discussionmentioning
confidence: 99%
“…This transient increase is likely due to the learning-induced expression of the transcription factor CREB (Rashid et al ., 2016; Silva et al ., 2009; Han et al ., 2007), which is known to play a role in regulating neural excitability (Dong et al ., 2006). As a result, time-varying excitability may account for overlapping neural ensembles encoding memories of events that are temporally linked (Sehgal et al ., 2018), namely events spaced by a short temporal delay, as observed in the lateral amygdala (Rashid et al ., 2016), the hippocampal dorsal CA1 (Cai et al ., 2016; Shen et al ., 2022), and the retrosplenial cortex (Sehgal et al ., 2021). Previous theoretical works have described how the dynamics of plasticity-related proteins and excitability can lead to co-allocation of memories at the dendritic level (Kastellakis et al ., 2016; Sehgal et al ., 2021; Chowdhury et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations